1999
DOI: 10.1046/j.1365-3040.1999.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between increasing CO2 concentration and temperature on plant growth

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
307
2
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(334 citation statements)
references
References 182 publications
(288 reference statements)
19
307
2
6
Order By: Relevance
“…Therefore, global warming is likely to influence plant growth through direct effects on metabolic rates, such as photosynthesis, respiration, and nutrient and water uptake (Llorens et al, 2004). Additionally, temperature is a key factor that regulates ontogenetic development rate (Morison and Lawlor, 1999). Previous studies have reported that experimental warming accelerated organ initiation and expansion rates (Wada et al, 2002;Llorens et al, 2004;Xu et al, 2009).…”
Section: Direct Warming Effect Through Stimulating Growth Ratementioning
confidence: 99%
“…Therefore, global warming is likely to influence plant growth through direct effects on metabolic rates, such as photosynthesis, respiration, and nutrient and water uptake (Llorens et al, 2004). Additionally, temperature is a key factor that regulates ontogenetic development rate (Morison and Lawlor, 1999). Previous studies have reported that experimental warming accelerated organ initiation and expansion rates (Wada et al, 2002;Llorens et al, 2004;Xu et al, 2009).…”
Section: Direct Warming Effect Through Stimulating Growth Ratementioning
confidence: 99%
“…High temperatures give rise to smaller and fibrous leaves that indicates changing of nutritional quality like reducing nitrogen and increasing tannins and phenols [30].…”
Section: E5 Tanninsmentioning
confidence: 99%
“…This question is currently open to debate (Clark 2004). Finally, some evidence suggests that higher CO 2 concentrations may reduce respiration, although there is much uncertainty over this (Morison & Lawlor 1999;Chambers & Silver 2004). …”
Section: (I) Temperature Effects On Photosynthesismentioning
confidence: 99%